Analysis of the impact of information communication technology on economic growth: empirical evidence from Asian countries - Kurniawati, Meta Ayu (University of Economics Ho Chi Minh City, 2023)
Purpose This study examines the causal relationship between information communication technology (ICT) and economic growth in high-income and middle-income Asian countries. Design/methodology/approach This study utilises a high-quality data from 25 Asian countries from 2000 to 2018. This study presents the robustness results by employing panel cointegration and estimation procedures to account for the endogeneity and cross-sectional dependence issues. Findings The results illustrate that high-income Asian countries have achieved positive and significant economic development from high Internet penetration. Additionally, the middle-income countries have started to benefit from ICT Internet. The findings show that the telephone line and mobile phone penetration is highly capable of promoting economic growth in middle-income Asian countries. Practical implications In high-income Asia countries, an appropriate ICT infrastructure policy will support feasible ICT penetration, which may drive the processes of economic development and innovation that contribute to economic growth. Moreover, in middle-income Asian countries, the establishment of better-quality ICT service and infrastructure is more critical. Policymakers should accommodate sufficient support to establish the ICT infrastructure and expand ICT penetration. Originality/value This study reveals that high-income Asian countries have been more proactive and effective than middle-income countries in embracing ICT to foster economic growth. Examining the case of high-income and middle-income Asian countries provides comprehensive insight for policymakers regarding the relevance of ICT in boosting economic growth through the advantages of technology expansion.